GAYA DESAIN COVER BUKU KARYA DJENAR MAESA AYU TAHUN 2016 - Tias Puji Astuti; Ana Rosmiati (TEXTURE : Art and Culture Journal, 2019)
ABSTRACTThe cover of Djenar Maesa Ayu’s literary book, released in 2016 entitled They Say I’m a Monkey!, Nayla, Don’t Play (Gently), and Short Stories About Love Stories Short, the illustrations that appeared in 2016 were a redrawing of the cover design in 2012. The visualization comparison displayed by the two covers in 2012 and 2016 are radically different. The main body of this research is an analysis of the design style in 2016. The research was conducted two stages, comparing the two covers and describing the concept of design style in the form of ilustration, typography, and color.Key Words: Design Style, Cover Design, Djenar Maesa AyuABSTRAKCover buku karya sastra Djenar Maesa Ayu tahun 2016 berjudul Mereka Bilang, Saya Monyet!, Nayla, Jangan Main-Main (Dengan Kelaminmu), Cerita Pendek Tentang Cerita Cinta Pendek merupakan penggambaran ulang dari desain cover tahun 2012. Perbandingan visualisasi kedua cover tahun 2012 dan 2016 memiliki gaya desain yang signifikan. Gaya desain cover tahun 2016 menjadi fokus utama analisis penelitian. Penelitian dilakukan dengan dua tahapan yakni membandingan kedua cover dan mendeskripsikan konsep gaya desain berupa ilustrasi, tipografi dan warna.Kata Kunci: Gaya Desain, Desain Cover, Djenar Maesa Ayu